Invasive Meningioma of the Infratemporal Fossa. Case Report and Review of the Literature (London Journal of Medical and Health Research, 2025)
Introduction: Meningiomas are common tumors of the central nervous system, originating from the meningotheleal cells of the arachnoid. Most meningiomas are benign and develop within the skull; some may extend extracranially, an unusual behavior that poses challenges in both diagnosis and treatment.Case report: We present the case of a 51-year-old woman with a meningioma in the right temporal and zygomatic region, which was initially asymptomatic. Imaging studies revealed an invasive lesion to the bone and soft tissues of the temporal region, including the orbit and infratemporal fossa. The patient underwent a two-stage surgery, achieving a subtotal resection of the tumor, which was reported as fibrous meningioma.Discussion: Although extracranial meningiomas are rare, they can arise as an extracranial extension of intracranial tumors or occur primarily outside the central nervous system (CNS). This poses a considerable diagnostic challenge due to its atypical location and lack of initial neurological symptoms, which may delay its detection. Meningiomas with extracranial and transosseous extension have a higher risk of surgical complications, and complex surgical approaches, such as orbitozygomatic craniotomies and multistage resections, have been shown to be necessary to achieve adequate resection and reduce recurrences.Conclusion: Surgical resection of these tumors is challenging due to their extent, underscoring the importance of a multidisciplinary therapeutic approach.
Keywords: Multiple Trauma; Accidents; Emergency Medicine.; secondary glaucoma; uveitis; posner-schlossman syndrome; intraocular pressure; topical corticosteroids.